The Second Sonata for Piano and Violin, Ópus 6 by George Enescu - Ioniță Raluca Dobre (Sciendo, 2021)
The second Sonata for Piano and Violin, op. 6 by George Enescu marks the beginning of a long road of assimilation and synthesis of the Romanian folklore elements and of the way of expression"in Romanian popular character", transposed on the characteristics of the universal language. Without knowing the authentic folk art from a scientific point of view, Enescu was deeply influenced, shaping his entire artistic personality. He consciously assimilated popular music by generalizing some essential folkloric principles, which he later organized in a personal vision. The innovative elements of the Enescian musical language are transposed in the free rhythm, the heterophonic construction, the complexity and subtleties of dynamics and agogics, the timbre color, as well as in the synthesis between freedom and rigor in the creative and interpretive act.